Sengketa Paten dan Upaya Penyelesaiannya : Analisis Hukum Indonesia dalam Sengketa Apple vs Massimo - May Lany Putri Carrlyn Hondro; Safira Arta Azzahra; Nadhira Wahyu Adityarani (Pusat Riset dan Inovasi Nasional, 2025)
Patent rights are a part of Intellectual Property Rights (IPR) that provide legal protection for inventions in the field of technology. With the rapid development of the times and technological advancements, the protection of patent rights has become an increasingly crucial issue. This is due to the growing number of patent infringements, particularly in the digital and medical device sectors, which often involve major global technology companies. One such case is the patent dispute between Apple Inc. and Masimo Corporation. The patent conflict between Apple and Masimo serves as a concrete example of how disputes over the ownership of technology can lead to complex legal issues, while also demonstrating how legal systems in developed countries respond to alleged patent infringements relatively effectively. On the other hand, Indonesia, as a developing country, still faces various challenges in resolving patent disputes, ranging from policy aspects and law enforcement processes to the capacity of existing institutions. This study aims to evaluate the extent to which Indonesia's patent legal system has been able to meet the demands of the times. Through the analysis of the Apple vs. Masimo case, this paper seeks to examine how Indonesia’s patent dispute resolution system can be strengthened to address global dynamics.